The Legal Policy of Criminal Justice Bureaucracy Cybercrime - Raharjo, Agus; Bintoro, Rahadi Wasi; Tri Utami, Nurani Ajeng (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2022)
Cybercrime has resulted in astronomical losses for the business community. However, the reactive policy model must be more effective at preventing cybercrime, and the due process model is also inappropriate for combating cybercrime with a high level of speed and mobility. This study is normative legal research employing a conceptual strategy and case studies. The results indicate that the reactive model must be improved in order to prevent cybercrime. The model of due process is not appropriate for deterring cybercrime with a high degree of speed and mobility. The preventative law enforcement strategy is effective, but it requires a high level of law enforcement capability to detect and disable cybercrime, which is something that few Indonesian law enforcement officials possess. Prevention based on the user, which places responsibility on internet users, is fine for individuals but not for businesses. Based on collaboration between corporations, universities, civic society, and non-governmental groups, the collaborative model synthesizes the aforementioned paradigms. Because they are based on plans or roadmaps created by internet stakeholders, regulations, technical aspects, and law enforcement may be effectively implemented and developed.